2021
DOI: 10.1590/1678-7757-2020-0734
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tooth movement and biological response resulting from different force magnitudes combined with osteoperforation in rabbits

Abstract: Comparison of tooth movement and biological response resulting from different force magnitudes combined with osteoperforation in rabbits Objective: To compare tooth movement rate and histological responses with three different force magnitude designs under osteoperforation in rabbit models. Methodology: 48 rabbits were divided into three groups: Group A, Group B, and Group C, with traction force of 50 g, 100 g, 150 g, respectively.Osteoperforation was performed at the mesial of the right mandibular first premo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Two studies were excluded due to reporting data in an unacceptable format. 9 , 17 Two studies used 100 g, two articles used 50 g for traction force, and just HUANG et al, evaluated 3 different traction forces including, 50, 100, and 150 g. 18 , 19 , 20 , 21 , 22 Additional assessment of TM, tartrate-resistant acid phosphatase (TRAP)-positive osteoclast count, and bone volume fraction were evaluated in three studies. 18 , 19 , 21 , 23 Finally, the main properties of six articles on 210 animals included in this meta-analysis with a wide range of species such as rat (n = 3), beagle dog (n = 1), and rabbit (n = 2) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies were excluded due to reporting data in an unacceptable format. 9 , 17 Two studies used 100 g, two articles used 50 g for traction force, and just HUANG et al, evaluated 3 different traction forces including, 50, 100, and 150 g. 18 , 19 , 20 , 21 , 22 Additional assessment of TM, tartrate-resistant acid phosphatase (TRAP)-positive osteoclast count, and bone volume fraction were evaluated in three studies. 18 , 19 , 21 , 23 Finally, the main properties of six articles on 210 animals included in this meta-analysis with a wide range of species such as rat (n = 3), beagle dog (n = 1), and rabbit (n = 2) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 32 Whereas, In two of included studies, the highest TM was seen with 50 g force after 2 weeks. 20 , 22 In this line, to evaluate the effect of increasing force on TM, Haung et al assessed the rate of TM after 50, 100, and 150 g force; they found that by increasing applied force, the TM not changed significantly. 22 The evidence presented in this section suggested that there is very low supporting positive correlation between root resorption and applied force.…”
Section: Clinical Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal selection, management, and operation protocols have carried out in accordance with the Animal Care Center's policy standard at Duhok University's Basic Science Department. After a one-month adaption period, the study's experimental portion was begin (Huang et al, 2021;Abtahi et al, 2018).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The reports suggest that MOPs accelerate OTM effectively. Perforations to the alveolar bone around the teeth have also been reported to accelerate OTM in experimental animal models [ 11 , 14 , 15 , 16 , 17 ]. Perforation procedures of the alveolar bone were found to induce expression of inflammatory cytokines because of enhanced osteoclast formation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%